Evaluation of Student Satisfaction with Aspects of Learning, Facilities, and Administration in the Pre-Service Teacher Professional Education Program - Yuniawatika, Yuniawatika; Prestiadi, Dedi; Hanafi, Yusuf; Alfan, Muhammad; Nofitasari, Natalia; Sari, Nanda Ayu Kartika; Febrianti, Fernanda Olivia (Teaching, Learning, and Development, 2026)
The pre-service teacher professional education program is organized with the support of academic systems, administration, and learning facilities designed to optimally meet the needs of students. This study aims to evaluate the level of student satisfaction with the learning process, academic administration services, and supporting facilities in the implementation of pre-service teacher professional education program. The method used was a quantitative descriptive survey involving 402 respondents. The instrument in the form of an online questionnaire was developed in an internal information system that contained 10 questions and one comment column. Data analysis was carried out in a qualitative and thematic manner. The results showed that the learning aspect obtained a very high level of satisfaction, especially in the ability of lecturers to convey material and guide practice. Administrative services are considered efficient, but students propose improvements in the clarity of schedules and coordination between parties. Learning facilities including classrooms and technology access were considered adequate, although some records suggested technical improvements and the addition of supporting facilities. These findings underline that the quality of learning, service effectiveness, and availability of facilities need to be seen as a complementary unit in supporting the quality of pre-service teacher professional education program implementation. Students' perceptions of these three aspects provide a valuable reflective foundation in the process of evaluating and formulating program management policies in a sustainable manner. This study recommends the development of advanced information systems that are relevant to quality assurance mechanisms in a structured and sustainable manner.